PACAP and VIP Neuropeptides’ and Receptors’ Effects on Appetite, Satiety and Metabolism - John P. Vu; Leon Luong; Daniel Sanford; Suwan Oh; Alma Kuc; Rita Pisegna; Michael Lewis; Joseph R. Pisegna; Patrizia M. Germano (Biology, 2023)
The overwhelming increase in the prevalence of obesity and related disorders in recent years is one of the greatest threats to the global healthcare system since it generates immense healthcare costs. As the prevalence of obesity approaches epidemic proportions, the importance of elucidating the mechanisms regulating appetite, satiety, body metabolism, energy balance and adiposity has garnered significant attention. Currently, gastrointestinal (GI) bariatric surgery remains the only approach capable of achieving successful weight loss. Appetite, satiety, feeding behavior, energy intake and expenditure are regulated by central and peripheral neurohormonal mechanisms that have not been fully elucidated yet. Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) and Vasoactive Intestinal Polypeptide (VIP) are members of a family of regulatory peptides that are widely distributed in parallel with their specific receptors, VPAC1R, VPAC2R and PAC1R, in the central nervous system (CNS) and in the periphery, such as in the gastrointestinal tract and its associated organs and immune cells. PACAP and VIP have been reported to play an important role in the regulation of body phenotype, metabolism and homeostatic functions. The purpose of this review is to present recent data on the effects of PACAP, VIP, VPAC1R, VPAC2R and PAC1R on the modulation of appetite, satiety, metabolism, calorie intake and fat accumulation, to evaluate their potential use as therapeutic targets for the treatment of obesity and metabolic syndrome.